Beyond Maastricht: How to strengthen Europe's sovereignty - Max Krahé (Dezernat Zukunft e.V., 2024)
Strengthening Europe's sovereignty has become a much-debated policy goal. This paper adds three arguments to ongoing discussions. First, it is no coincidence that recent years have witnessed increasing debate around how to strengthen Europe's sovereignty. The Maastricht-EU, Europe's overarching political order since the 1990s, aimed to overcome sovereignty, not to strengthen it. In a context of war and an industrial policy renaissance, this ambition is obsolete. Sovereignty lies beyond Maastricht. Second, the debate around external sovereignty, i.e. power and its material base, would benefit from stronger integration with debates on internal sovereignty, i.e. legitimacy and institutional reform. Without clear and legitimate decision-making structures, even a strong material and technological base fails to provide self-determination or security. Third, reforming and clarifying decision-making structures in Europe is politically challenging. To achieve progress, transparent horse-trading seems the most promising path forward: the shifting or sharing of competences based on openly avowed self-interest. Such horse-trading is complex. A lack of trust at various levels further complicates negotiations. In this context, civil society and academia can help by analysing possible elements of such horse-trading - for example, in the areas of energy, finance, defence or industrial policy - to offer an outsider's view on who wins and who loses under respective options.
Keywords: 330; sovereignty; europe; fiscal; security; energy